Analysis of MTHFR and MTRR gene polymorphisms in Iranian ventricular septal defect subjects - Pishva, Seyyed Reza; Vasudevan, Ramachandran; Etemad, Ali; Heidari, Farzad; Komara, Makanko; Ismail, Patimah; Othman, Fauziah; Karimi, Abdollah; Sabri, Mohammad Reza (MDPI, 2013)
Ventricular septal defect (VSD) is one of the most common types of congenital heart defects (CHD). There are vivid multifactorial causes for VSD in which both genetic and environmental risk factors are consequential in the development of CHD. Methionine synthase reductase (MTRR) and methylenetetrahydrofolate reductase (MTHFR) are two of the key regulatory enzymes involved in the metabolic pathway of homocysteine. Genes involved in homocysteine/folate metabolism may play an important role in CHDs. In this study; we determined the association of A66G and C524T polymorphisms of the MTRR gene and C677T polymorphism of the MTHFR gene in Iranian VSD subjects. A total of 123 children with VSDs and 125 healthy children were included in this study. Genomic DNA was extracted from the buccal cells of all the subjects. The restriction fragment length polymorphism polymerase chain reaction (PCR-RFLP) method was carried out to amplify the A66G and C524T polymorphism of MTRR and C677T polymorphism of MTHFR genes digested with Hinf1, Xho1 and Nde1 enzymes, respectively. The genotype frequencies of CC, CT and TT of MTRR gene among the studied cases were 43.1%, 40.7% and 16.3%, respectively, compared to 52.8%, 43.2% and 4.0%, respectively among the controls. For the MTRR A66G gene polymorphism, the genotypes frequencies of AA, AG and GG among the cases were 33.3%, 43.9% and 22.8%, respectively, while the frequencies were 49.6%, 42.4% and 8.0%, respectively, among control subjects. The frequencies for CC and CT genotypes of the MTHFR gene were 51.2% and 48.8%, respectively, in VSD patients compared to 56.8% and 43.2% respectively, in control subjects. Apart from MTHFR C677T polymorphism, significant differences were noticed (p < 0.05) in C524T and A66G polymorphisms of the MTRR gene between cases and control subjects.